Crossmodal Association Between Linguistic Sounds and Motion Imagery: Voicing in Obstruents Connects With Different Strengths of Motor Execution. (June 2019) - Yamauchi, Naoto; Shinohara, Kazuko; Tanaka, Hideyuki
The present study investigates whether obstruent voicing may or may not affect the imagery of different strengths of motor execution. In a modified version of the implicit association test, participants responded to discrimination tasks that include viewing static pictures of athletes in motion and hearing mono-syllabic linguistic sounds. The results suggest that voiced obstruents are compatible with the motion imagery that implies stronger motor executions, whereas voiceless obstruents are compatible with the imagery that implies weaker motor executions. These results provide experimental support for crossmodal associations between the auditory perception of linguistic sounds, namely, the voicing of obstruents, and the visually induced imagery of different levels of strength in motor actions.